Method of image reconstruction based on two-level decoding of linear transforms - Turenko, Sergey Viktorovich; Barannik, Vladimir Viktorovich (Ukrainian Information Security Research Journal, 2014)
This paper deals with the main stages of developing the method of image segment reconstruction on the basis of decoding oftruncated double tuple vectors. It has been proved that the method must include the following distinctive stages: installation of codedesign; decoding of code values of the component of double tuple truncated vectors; reconstruction of double tuples based on decodingthe biadic numbers. Installation process, which includes the following actions, is created: selection of an auxiliary part;decomposition of an information part of code design, namely determination of: number of code words; last codegram of non-uniformlength; withdrawal of code words.